1998
DOI: 10.1016/s0925-4773(98)00053-7
|View full text |Cite
|
Sign up to set email alerts
|

In Drosophila, female gonadal cells repress male-specific gene expression in XX germ cells

Abstract: In Drosophila, the sex of XX germ cells is determined by somatic signals. Whether sex-specific genes, however, are activated or repressed by somatic signals is not known. We have used mgm1, a germline-marker which is specifically expressed in male germ cells to analyze sex-specific gene expression of embryonic germ cells. We found that XX and XY germ cells that do not contact gonadal tissue can express mgm1. In contrast, XX germ cells that were associated with female somatic gonadal cells never expressed mgm1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…3B). This repression has also been observed with mgm-1 (Heller and Steinmann-Zwicky, 1998). In addition, XY germ cells exhibit some female-specific otu expression when in contact with a female soma (UAS-tra, Fig.…”
Section: (This Work)supporting
confidence: 68%
See 3 more Smart Citations
“…3B). This repression has also been observed with mgm-1 (Heller and Steinmann-Zwicky, 1998). In addition, XY germ cells exhibit some female-specific otu expression when in contact with a female soma (UAS-tra, Fig.…”
Section: (This Work)supporting
confidence: 68%
“…We used the newly identified sexspecific molecular markers to determine how these two components contribute to the establishment of germline sexual identity in the embryo. Previous studies have shown that mgm-1 is expressed in both XX and XY germ cells that are not in contact with the somatic gonad, suggesting that male identity in the germline is the 'default' in the absence of the somatic gonad (Heller and Steinmann-Zwicky, 1998).…”
Section: Autonomous Sex Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…XY germ cells initiate mgm1 expression even in a female somatic environment, indicating that it is regulated by the germ cell genotype (Heller and Steinmann-Zwicky, 1998;Janzer and Steinmann-Zwicky, 2001). mgm1 expression is also regulated by the soma, as XY germ cells cannot maintain mgm1 expression in a female soma (Janzer and Steinmann-Zwicky, 2001).…”
Section: Initial Germ Cell Sexual Identitymentioning
confidence: 99%